Strategi Pembelajaran Bahasa Arab Berbasis Internet - Ahmad Taufik (Edification Journal : Pendidikan Agama Islam, 2020)
In the activities of the Arabic learning process, there needs to be language skills that can be fulfilled in language learning, namely listening skills (al-istima '), speaking (al-kalam), reading (al-qira'ah), and writing (al- kitabah). With the Internet media all educational needs will arise broad knowledge, especially in developed countries, is the fact this internet shows that this media helps the learning process more effectively.Through the internet Interaction between teachers and students, for example assignments and work assignments can also be done via the internet.